Integrating the Eastern Länder - Siebert, Horst (Inst. für Weltwirtschaft, 1994)
Lit.
Literaturverz. S. 16
Keywords: Graue Literatur; Buch; Konferenzschrift; Wirtschaftliche Anpassung; Prognose; Ostdeutschland; Wiedervereinigung; Vereinigung; Wirtschaftliche Integration; Strukturanpassung; Wirkung; Auswirkung; Wirtschaftspolitik